Comparative aspects of surgical treatment of the patients with thoracic aorta diseases - Vladimir Dikolayev; Adilzhan Albazarov; Turlybek Tuganbekov; Vladimir Grigorevsky; Kulsara Rustemova; Saule Nurakaeva; Murat Raikhanov (National Scientific Medical Center, 2019)
Objective: To carry out comparative analysis of the various surgical methods in patients with thoracic aorta pathology (aneurism, dilatation, dissection) in combination with bicuspid aortic valve in comparison to tricuspid aortic valve patients and to choose most appropriate approach of the surgical treatment in correlation with thoracic aorta sizes. Material and methods: In this work 212 case records of two patient groups with thoracic aorta pathology were analyzed, operated from 2013 until 2015 in cardiothoracic department of the "National Scientific Medical Center" JSC, to whom 4 surgical approaches were applied: Bentall de Bona procedure, supracoronary aorta replacement  procedure, David procedure, Borst procedure.   Results: Usage of  Bentall de Bona procedure in patients with  bicuspid aortic valve was related to less risk of postoperative complications in comparison with the group of tricuspid aortic valve patients (17,5% vs 39,5%, p=0,01). Surgical treatment with the usage of David procedure in observation group with BAV eliminates aortic valve insufficiency (degree of aortic valve insufficiency pre and postoperative - 2,3 ± 1,3 and 0,9 ± 1,1 respectively, p=0,04). Conclusion: Surgical treatment of thoracic aorta pathology in patients with bicuspid aortic valve (mainly with stenosis) with the usage of Bentall de Bona approach is accepted as reasonable because it eliminates most considerably the implications of aortopathy and in this regard considered to be the most effective. David procedure is indicated to patients with pathology of thoracic aorta in combination with bicuspid aortic valve (mainly with insufficiency).